Economic Burden Attributed to Children Presenting to Hospitals With Hand, Foot, and Mouth Disease in Vietnam. (13th June 2019) - Nhan, Le Nguyen Thanh; Turner, Hugo C; Khanh, Truong Huu; Hung, Nguyen Thanh; Lien, Le Bich; Hong, Nguyen Thi Thu; Nhu, Le Nguyen Truc; Ny, Nguyen Thi Han; Nguyet, Lam Anh; Thanh, Tran Tan; Van, Hoang Minh Tu; Viet, Ho Lu; et al.
Abstract: Background: Hand, foot, and mouth disease (HFMD) has become a major public health concern in the Asia-Pacific region. Knowledge of its economic burden is essential for policy makers in prioritizing the development and implementation of interventions. Methods: A multi-hospital-based study was prospectively conducted at 3 major hospitals in Ho Chi Minh City, Vietnam, during 2016–2017. Data on direct and productivity costs were collected alongside clinical information and samples and demographic information from study participants. Results: A total of 466 patients were enrolled. Two hundred three of 466 (43.6%) patients lived in Ho Chi Minh City, and 72/466 (15.5%) had severe HFMD. An enterovirus was identified in 74% of 466 patients, with EV-A71, CV-A6, CV-A10, and CV-A16 being the most common viruses identified (236/466, 50.6%). The mean economic burden per case was estimated at US$400.80 (95% confidence interval [CI], $353.80–$448.90), of which the total direct (medical) costs accounted for 69.7%. There were considerable differences in direct medical costs between groups of patients with different clinical severities and pathogens (ie, EV-A71 vs non-EV-A71). In Vietnam, during 2016–2017, the economic burden posed by HFMD was US$90 761 749 (95% CI, $79 033 973–$103 009 756). Conclusions: Our findings are of public health significance because for the first time we demonstrate that HFMD causes a substantial economic burden in Vietnam, and although multivalent vaccines are required to control HFMD, effective EV-A71 vaccine could substantially reduce the burden posed by severe HFMD. The results will be helpful for health policy makers in prioritizing resources for the development and implementation of intervention strategies to reduce the burden of HFMD.